Process mapping and business process re-engineering training needs analysis for ERP system providers. - Obibi, Ndidi Ogechi (Cranfield University, 2002)
This thesis presents the results of a collaborative research project and documents a process mapping exercise on Training Needs Analysis as utilised during the implementation of ERP projects. In the first instance, it focuses on capturing the activities involved in delivering an effectively tailored Training Needs Analysis (TNA). The documented methodology then forms a foundation for understanding the main activities within the Training Needs Analysis process and is later investigated as a means to carrying out comparative analysis in identifying opportunities for improvements. The research then proceeds to investigate state of the art literature on the assumed role attributed to the outputs of the Training Needs Analysis process as an unframed evaluative methodology for measuring the success and or failure of planned ERP implementation projects. Through the review of available literature, evolves an analysis on the availability and suitability of tools used for evaluating the success or failure of ERP projects or indeed the lack of such tools. The research goes further, seeking to understand the relationship between what is seen as the evaluation process for a successful ERP implementation project in relation to a successful Training Needs Analysis process, while investigating the data gathering processes utilised during the analysis. Finally, addressing some of the unspoken and expected outcomes which may be sought or attributed to the Training Needs Analysis process, the research project concludes by analysing the AS-IS Training Needs Analysis process alongside documented best practices, before initiating subsequent process improvement exercises and Business Process Re-engineering techniques as methodologies for recommending a more suited TO-BE framework for the Training Needs Analysis process map. Recommending both a continuous and evolving process framework, it goes further allowing for a more structured evaluation in the results or quality of a Training Needs Analysis process which are created in-line with the opportunities for improvements identified in the evaluation phase.